Blueberry pectin and increased anthocyanins stability under in vitro digestion. (1st January 2020) - Koh, Jeewon; Xu, Zhimin; Wicker, Louise
Highlights: Malvidin-, cyanidin-, and delphinidin-3-glucosides uniquely bind pectin fractions. In vitro stability was highest with chelator soluble fraction and cyanidin-3-glucoside. Chelator soluble fraction protected anthocyanin stability more than water soluble fraction. Hydrogen bond contributes strongly to blueberry pectin-anthocyanin interaction at pH 4.0. Abstract: Pectin was extracted from blueberry powder as water soluble fraction (WSF), rich in branched regions, and chelator soluble fraction (CSF), linear, with strong negative charge. Binding of pectins with three anthocyanin standards (malvidin-3-glucoside; M3G, cyanidin-3-glucoside; C3G, and delphinidin-3-glucoside; D3G) and blueberry extract (BBE) were used. Without blueberry pectin, M3G was the most stable followed by C3G, whereas D3G completely disappeared after gastrointestinal digestion. CSF prevented M3G and C3G degradation more than WSF, the in vitro stability was highest with CSF and C3G. Increased stability of anthocyanins after simulated gastrointestinal digestion suggests that anthocyanins can be transported to colon where gut microbiota actively produce anthocyanin metabolites. The amount of bound anthocyanins that interacted with blueberry pectin increased as the number of hydroxyl groups increased on anthocyanins. Hydrogen bonding in addition to electrostatic interaction contribute to stability of pectin-anthocyanins interaction at pH 4.0 and contribute to stability under gastrointestinal simulation.